Bashkir Theme in Works by P.L. Yudin, Orenburg Local Historian of the Beginning of the XX Century - Viktoriya Y. Prokofeva; Alla G. Prokofeva (Publishing house "Sreda", 2020)
The article presents data on the studies by P.L. Yudin, a Russian historian-archivist of the beginning of the 20th century, local historian, a member of several scholarly archival commissions, who being a native of the Orenburg Region, dedicated his scientific activity to the study of multinational South Ural. For the first time, the Bashkir theme - research about the culture, history and people of Bashkiria - stands out in the scientist's legacy. Methods of research: analysis of the works of the scientist about Bashkir history, its culture and people, published in the magazines, newspapers. Based on the analysis of scientist's works the following aspects of the study of Bashkiria by P.L. Yudin are distinguished: the historical past of the region - the settlement of Bashkir lands, a description of the Bashkir cities, the lives and mode of life of their inhabitants, archival data on the participation of the Bashkirs in the Pugachev uprising, the personality of V.A. Perovsky, Orenburg military governor general of the early 19th century, his military campaigns and citations about him in Bashkir history, historical visits to the Ufa Governorate by historical figures, including Emperor Alexander I, preparation for such visits, religious beliefs of the Bashkir population. Conclusion. The importance of studies by P.L. Yudin and the relevance of his archival finds for ethnography, ethnology and modern historical science is denoted as well.